The Role of Teachers in Fostering Digital Literacy and Citizenship among Elementary School Students - Prince Clinton Immanuel Christian Damanik; Mohammad Idham Chaled; Feri Dwi Jayanti; Rizki Achmad Husaeni; Anastasia Arta Uli (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
The rapid growth of digital technology over the past decade has transformed both social and educational life, especially among elementary school students who are increasingly exposed to digital devices and social media. While these technologies offer opportunities for creativity, communication, and information access, they also present risks such as misinformation, cyberbullying, and digital addiction. This study explores the role of teachers in fostering digital literacy and citizenship among elementary school students. Using a qualitative descriptive approach, data were gathered through in-depth interviews and classroom observations involving elementary school teachers in Jakarta. Thematic analysis was employed to identify teachers’ strategies, roles, and challenges in nurturing students’ digital literacy and civic responsibility. The findings reveal that teachers serve as educators, facilitators, and role models who promote responsible and ethical digital behavior through project-based learning, digital storytelling, moral modeling, and the creative use of interactive media. However, challenges such as limited teacher competence, insufficient contextual teaching materials, and low parental engagement remain. The study highlights the need to strengthen teacher training in digital ethics and pedagogy and offers practical implications for policymakers to enhance digital education aligned with Indonesia’s Pancasila Student Profile.